1980
DOI: 10.1002/anie.198000691
|View full text |Cite
|
Sign up to set email alerts
|

6‐Fulveneselone

Abstract: Highly reactive fulveneselone (2) has been generated from benzoselenadiazole (1) by vacuum flash thermolysis and characterized by PE spectroscopy. The dark red species (2) reacts with explosive violence to give a brown polymer at as low a temperature as 77 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…16 The stoichiometric reaction of m-diisopropenylbenzene with two moles of sec-butyllithium has been reported to produce a useful, hydrocarbon-soluble dilithium initiator because of the low ceiling temperature of the m o n~m e r~~~~~ which is analogous in structure to a-methylstyrene; however, other studies suggest that oligomerization occurs with this divinyl compound also and that functionalities higher than two result.27 Higher functionalities have also been reported for the analogous precursor, 1,lbis(4-isopropenylphenyl)-l-phenyltride~ane.~~ A plethora of divinyl aromatic compounds have been evaluated as precursors for hydrocarbonsoluble dilithium initiators' without the emergence of a simple, stable, reproducible initiating system until recent work with 1,3-bis( 1-phenyletheny1)benzene. [29][30][31][32][33][34] The addition reaction of sec-butyllithium with 1,3-bis( 1-phenyletheny1)benzene (eqns (l), (2)) proceeds rapidly and efficiently to produce the corresponding dilithium species with a rate constant for the second addition (k,, eqn (2)) which is equal to the rate constant for the first addition (kl, eqn (1)) in toluene solution,35 but an order of magnitude larger in cy~lohexane.~' It has been reported that this dilithium initiator is not only soluble in hydrocarbon media such as cyclohexane, benzene and toluene (even at -20"C32), but also functions as an efficient difunctional initiator for the preparation of CH, CH, I 1 II 1 2 3 homopolymers and triblock copolymers with relatively narrow molecular weight distribution^.^' -3 1…”
Section: Introductionmentioning
confidence: 99%
“…16 The stoichiometric reaction of m-diisopropenylbenzene with two moles of sec-butyllithium has been reported to produce a useful, hydrocarbon-soluble dilithium initiator because of the low ceiling temperature of the m o n~m e r~~~~~ which is analogous in structure to a-methylstyrene; however, other studies suggest that oligomerization occurs with this divinyl compound also and that functionalities higher than two result.27 Higher functionalities have also been reported for the analogous precursor, 1,lbis(4-isopropenylphenyl)-l-phenyltride~ane.~~ A plethora of divinyl aromatic compounds have been evaluated as precursors for hydrocarbonsoluble dilithium initiators' without the emergence of a simple, stable, reproducible initiating system until recent work with 1,3-bis( 1-phenyletheny1)benzene. [29][30][31][32][33][34] The addition reaction of sec-butyllithium with 1,3-bis( 1-phenyletheny1)benzene (eqns (l), (2)) proceeds rapidly and efficiently to produce the corresponding dilithium species with a rate constant for the second addition (k,, eqn (2)) which is equal to the rate constant for the first addition (kl, eqn (1)) in toluene solution,35 but an order of magnitude larger in cy~lohexane.~' It has been reported that this dilithium initiator is not only soluble in hydrocarbon media such as cyclohexane, benzene and toluene (even at -20"C32), but also functions as an efficient difunctional initiator for the preparation of CH, CH, I 1 II 1 2 3 homopolymers and triblock copolymers with relatively narrow molecular weight distribution^.^' -3 1…”
Section: Introductionmentioning
confidence: 99%